Improving Students Activity and Students Learning Outcomes by Using Peer Tutor Base on Polya Model - Siti Maisyaroh (Universitas Islam Jember, 2020)
The purpose of the research to know the using of peer teaching base on polya model can increasing the students’ activities and to know the using of peer teaching base on polya model can increasing the students learning outcomes. The kind of the research is PTK with quantitative approach. The subjects of the research are students of class VII at MTs Zainul Irsyad Warujinggo Leces Probolinggo. With the data collecting method that used in the research are documentation, observation, interview and test. The data analysis method that used is quantitative. The results of the research there is increased activity and mathematical student learning outcomes.Keywords: peer tutor base on polya model, students activity, and learning outcomes